Evaluating household residential preferences for walkability and accessibility across three U.S. regions. (March 2020) - Yan, Xiang
Highlights: Walkability, transit accessibility, and auto accessibility all shape residential location choice. Regional context plays an important role in shaping the estimates of residential preferences. Auto accessibility to nonwork destinations appears to be inconsequential in residential location choice. Walkability is a highly significant predictor of residential location choice in Puget Sound but not in Atlanta and Southeast Michigan. Due to housing-supply constraints, households often have to live in a neighborhood with a level of accessibility lower than desired. Abstract: Accessibility has been established as a major planning goal in recent years. However, little knowledge exists regarding how individuals value walkability, transit accessibility, and auto accessibility differently when deciding where to live. To fill this knowledge gap, this study conducts residential location choice modeling across three U.S. regions—Atlanta, Puget Sound, and Southeast Michigan. I find that, overall, all three types of accessibility are important determinants of residential location choice. Transit accessibility has a statistically significant positive influence on residential location choice across all three regions. On auto accessibility, results show that commute time by auto has the greatest influence on residential location choice among all independent variables, but auto accessibility to nonwork destinations appears to be inconsequential. Moreover, walkability is found to be a key determinant of residential location choice in the Puget Sound region but not the other two regions. I argue that these regional differences result from a lack of choice among Atlanta and Southeast Michigan residents, that is, a undersupply of walkable neighborhoods inhibits households in the two regions from living in such neighborhoods. This finding suggests the need for cities and regions to promote pedestrian-oriented development in order to broaden residential choice. The results further imply that, due to housing-supply constraints, households often have to live in a neighborhood with a level of accessibility lower than what they prefer. Transportation and land-use planners should address this "residential dissonance" when applying residential location choice models to predict land-use growth patterns.